CONSIDERATIONS REGARDING THE STRENGTH CALCULUS OF MILLING CUTTERS TEETH - Catălin ROŞU (Fiabilitate şi Durabilitate)
In this paper, I present a strength calculus for milling cutter teeth. I will consider the loadings that actupon the first tooth, when it removes the tooling allowance from the manufactured piece, because it is the mostloaded one. I will present all the steps that are made for the strength calculus. The simplifying assumptions andthe calculus relations (especially for the equivalent stress) are presented in an original way.